2020
DOI: 10.1097/mnm.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–based skeletal segmentation for quantitative PET metrics of bone involvement in multiple myeloma

Abstract: Purpose Quantifications in nuclear medicine are occasionally limited by the lack of standardization for defining volumes of interest (VOIs) on functional images. In the present article, we propose the use of computed tomography (CT)–based skeletal segmentation to determine anatomically the VOI in order to calculate quantitative parameters of fluorine 18 fluorodeoxyglucose (18F-FDG) PET/CT images from patients with multiple myeloma. Methods We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…This is at least partially explained by the fact that bone marrow is part of the normal biodistribution of FDG [ 28 , 29 ]. Quantitative methods have been proposed to overcome this issue, but still with some complexity for routine use [ 30 , 31 ]. Bone marrow is not part of the normal biodistribution of MIBI [ 28 ] and, as suggested by the present study, it seems to be a good alternative for assessing bone marrow involvement by multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…This is at least partially explained by the fact that bone marrow is part of the normal biodistribution of FDG [ 28 , 29 ]. Quantitative methods have been proposed to overcome this issue, but still with some complexity for routine use [ 30 , 31 ]. Bone marrow is not part of the normal biodistribution of MIBI [ 28 ] and, as suggested by the present study, it seems to be a good alternative for assessing bone marrow involvement by multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Total tumor burden analyses can be combined with specific organ segmentation either based on PET or CT, e.g. for spleen (for lymphoma) and bone, to generate organ-specific tumor burden (181,182). Furthermore, the segmentation leading to total tumor burden or organ-specific tumor burden can also be used as a mask to determine specific radiomic features, which can provide even more information for response evaluation (180).…”
Section: Beyond Recist and Percistmentioning
confidence: 99%
“…Takahashi et al [34] retrospectively assessed SUVmax, SUVmean and SD SUV in the whole skeleton of 101 MM patients using CT-based segmentation. They found that both SUVmean and SD SUV agree better than SUVmax with FDG-PET/CT visual analysis.…”
Section: 𝑆𝑈𝑉(𝑡) =mentioning
confidence: 99%
“…However, it can provide a good overview of the overall state of skeletal tumor burden, including slight increases in baseline values (Figure 2). [34,37]. (c) MIP of FDG-PET images after bone segmentation using CT.…”
Section: 𝑆𝑈𝑉(𝑡) =mentioning
confidence: 99%
See 1 more Smart Citation